Temporal patterns of bat activity on the High Plains of Texas - Julie A., Parlos; Macy A., Madden; Lizette, Siles; Faisal Ali, Anwarali Khan; Cibele G., Sotero-Caio; Kendra L., Phelps; Robert J., Baker; Robert D., Bradley (Museum of Texas Tech University, 2019)
Texas is home to more wind turbines and more bat species than any other state in the United States. Insectivorous bats provide an important economical ecosystem service in this region through agricultural pest regulation. Unfortunately, bats can be impacted negatively by wind turbines, and migratory bat species particularly so. To understand how bat activity changes throughout the year in western Texas, activity was monitored through echolocation calls and opportunistic mist-netting efforts over a period of four years (2012–2015). Peaks in activity were observed from March through April, and again in September, which coincides with previously documented migratory periods for many species native to the High Plains of Texas. Findings presented herein suggest that urban habitats are preferred stopover sites for migratory bat species while traversing arid regions such as those occurring in western Texas. In addition to human-made structures, urban habitats harbor non-native trees that provide suitable roost sites, aggregations of insect prey swarming outdoor light sources, and artificial water sources. It is important to understand bat activity in western Texas, not only for the benefit of agricultural pest suppression, but also to predict how the expansion of wind energy may affect bat populations in this region.